Digital Parenting Style Perspektif Al-Qur’an: Kajian Tafsir Tematik atas QS Luqman ayat 13-19 - NurKhalimah, Siti; Nurul Izzati, Isma; Maisya, Anis (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
ABSTRACT This study examines moral values ​​in QS. Luqman verses 13-19 as a basis for parenting in the digital era and formulates a digital parenting strategy based on Qur'anic principles that are relevant to the challenges of the times. The analysis was conducted qualitatively with descriptive data presentation. The maudhui interpretation method and Fazlur Rahman's double movement approach were used to connect historical and contemporary meanings. Data were collected through a study of the verses of the Qur'an and interpretations as well as from books and articles about Digital Parenting. The results of the study show that values ​​such as monotheism, gratitude, amar ma'ruf nahi munkar, and social etiquette in QS. Luqman verses 13-19 are relevant as a moral and spiritual basis in facing parenting challenges in the digital era, such as exposure to negative content, technology addiction, and declining moral character of children. These findings confirm that the integration of Qur'anic principles can strengthen ethical and empowering parenting strategies, as well as build children's character solidly morally and spiritually. In conclusion, strengthening moral values ​​from these verses is important for building a resilient young generation amidst the rapid development of technology. This study provides practical and theoretical contributions to the development of Qur'anic value-based parenting strategies in a digital context. Keyword: Digital parenting, thematic interpretation, QS. Luqman, digital era